Profil Klinikopatologik Keganasan Ampula Vateri dan Pankreas di RSUP Nasional Dr. Cipto Mangunkusumo Tahun 2015-2019 - Pramono, Meike; Rini Handjari, Diah (Majalah Patologi Indonesia, 2023)
Background Malignancies of ampulla of vater and pancreas are often difficult to distinguish. Malignancies in ampulla of vater include malignancies in major duodenal papilla, distal common bile duct and pancreatic duct opening (Wirsung). The origin of the primary tumor, histopathological diagnosis and staging play a role in therapy and prognosis. WHO Classification of tumors of the digestive system, 2019 made changes in tumor staging following the system of the American Joint Committee on Cancer (AJCC), 8th edition. This study was conducted to determine types of pancreatic and ampullary malignancies, demographic distribution, location, profile, histomorphology and tumor staging changes in the 7th edition of the AJCC to 8th edition of the AJCC in the WHO Classification of tumors of the digestive system, 2019. The aim to determine clinicopathological profile of malignancies of ampulla of vater and pancreas as well as tumor staging changes based on AJCC edition 8. Methods Observational descriptive study on pancreatic and ampulla vater malignancy resection preparations at Department of Anatomic Pathology FKUI/RSCM, period January 2015 to December 2019 that met the inclusion criteria. Demographic evaluation, tumor location, histopathological profile and patient staging changes were carried out based on the 8th edition of AJCC. Results There were 27 cases of adenocarcinoma in ampulla of vater, 10 cases of pancreatic ductal adenocarcinoma, 1 case of mucinous cystic neoplasm with adenocarcinoma focus, 1 case of serous cystadenocarcinoma, 7 cases of PanNET, 2 cases of PanNEC, 3 cases of SPN, 1 case of MiNEN. Changes in pT were present in 29 cases. Changes in pN were present in 6 cases. Conclusion The diagnosis and pathological staging are in accordance with the 2019 WHO digestive system tumor classification. Tumor differentiation, presence or absence of lymphovascular invasion, perineural invasion and lymph node metastases and incision margin status are important histopathological parameters.